Nanocápsulas e nanoesferas de disseleneto de difenila: síntese e distribuição biológica - Alves, Camila Ferrazza (2012)
In last years, selenium organic compounds of selenium have been targets of interest in organic synthesis because of their synthetic application and their pharmacological properties. Diphenyl diselenide (PhSe)2 is an organic compound of selenium that has several pharmacological effects; however the poor water-solubility and low oral bioavailability can be a limit for its clinical utility. Polymeric nanoparticles has been an impotant model to carry drugs with advantages such as increase bioavailability, targeting to specific sites and the possibility of encapsulation of lipophilic compounds quite efficiently. In view of the quest for developing a system to control drug release and improve its oral bioavailability, this study aims to prepare nanospheres and nanocapsules of (PhSe)2 by the interfacial deposition method of preformed polymer cores using different oils (miglyol, canola oil and omega-3) as the oil core. The nanocapsules will be characterized by measuring the pH, mean particle size, polydispersity index, zeta potential, rate of association and determination of (PhSe)2. By adjusting the process parameters, the results of the optimized formulation showed a size distribution with a polydispersity index of up to 0.2, an average diameter of less than 330 nm, zeta potential was greater at -16 mV, and encapsulation rate efficiency of 99.9 % found for all formulations developed. The biological tests performed in mice with the nanocapsules of (PhSe)2 containing canola oil as the oil core, showed increased bioavailability of the (PhSe)2 compared with the (PhSe)2 free, showing a proeminent influence of nanoparticle systems for biological properties of organochalcogenium compounds.